(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The poems of a blind woman from Grgurevci, some of the best poems Vuk Karadžić published in Vienna in 1845, are included in the literary and national canon to the greatest extent. The most famous details from her opus – Lazar’s choice of the Kingdom of Heaven and the image of Kosovka devojka (Kosovo Maiden) giving wine to the wounded from the golden goblet after the battle – are exclusive in epic corpus and remembered thanks to exceptional variations of this performer. Therefore, her contribution to cultural heritage is almost immeasurable. Nevertheless, these motives will not be (primarily) studied as elements of individual poetics because: 1) there is no way to determine if Slepa from Grgurevci (The Blind Woman from Grgurevci) introduced the motives herself or assumed them from one of her antecedents, and 2) oral literature is essentially supra-individual. Slepa from Grgurevci is a striking example of a much used practice of oral poets who transferred different and sometimes contradictory layers of tradition and relied on old formulas and plot patterns, while crossing numerous tradition branches.The analysis of the above mentioned motives in wider epic and Indo-European context will reveal great tension between these layers of tradition, as well as their position and semantic.